Soft Tissue Augmentation Using Free Mucosal Graft - Nadig, Prasad; Nadig, Priyadarshini (Journal of Orofacial Research, 2012)
Gingival augmentation procedures are indicated primarily to increase an insufficient amount of gingiva and sometimes to halt the progression of gingival recession. Inadequate orabsence of attached gingival is considered detrimental to periodontal health by many researchers. Individuals with less than optimal oral hygiene practice can be helped by increasingthe width of attached gingiva and vestibular depth, which provide room for easier placement of toothbrush and help to avoid brushing on mucosal tissue. This article puts emphasis on acase report where management of gingival recession and decreased width of attached gingiva was done by free mucosal graft with encouraging results.